Model Dinamika Pertumbuhan Penduduk terhadap Kebutuhan Lahan Permukiman dan Ruang Terbuka Hijau di Kecamatan Tanah Grogot Kabupaten Paser: Indonesia - Sari, Rina Ratna (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Population growth in Tanah Grogot District, Paser Regency, increases the need for residential land and green open space (RTH), which has the potential to put pressure on the environmental carrying capacity and capacity. This study aims to analyze the dynamics of population growth on land needs using a dynamic systems approach. The research method includes the preparation of a Causal Loop Diagram (CLD) to identify feedback relationships between variables and the development of a Stock and Flow Diagram (SFD) to simulate various policy scenarios. The variables analyzed include population size, growth rate, residential land needs, and green open space area. The simulation results show that without policy intervention, in 2075 the need for residential land is projected to reach 1.469,75 ha and green open space to reach 226,23 ha, with a land deficit of 412,44 ha. New land needs begin to occur in 2050 due to exceeding the capacity of available space, which indicates the potential for overshoot and degradation of ecological functions. The scenario of reducing the population growth rate from 1,74% to 1% is able to reduce the need for residential land to 1.097,07 ha and green open space to 172,10 ha, and delay the need for new land until 2060. Meanwhile, reducing the growth rate to 0,5% per year with a two-year delay also reduces spatial pressure and delays the deficit until 2065. This study concludes that controlling population growth plays an important role in maintaining the balance between development needs and environmental capacity. Integration of population policies with land use management and increasing green open space is needed to maintain the stability of ecological functions and support the sustainability of the urban environment